Handbook of the nations - United States. Central Intelligence Agency (Detroit : Gale Group/Thomson Learning, 2002)
Contains entries for 255 nations and their dependent areas, each with a map and data on the geography, people, government, economy, communications, transportation systems, military, and transnational issues.
"A brief guide to the economy, government, land, demographics, communications, and national defense establishment of each of 267 entities of the world.".
Adult
Keywords: Comparative government -- Handbooks, manuals, etc; Economic history -- Handbooks, manuals, etc; World history -- Handbooks, manuals, etc; Comparative government -- Handbooks, manuals, etc; Economic conditions -- Handbooks, manuals, etc; World history -- Handbooks, manuals, etc